2022
DOI: 10.1002/bse.3110
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for implementing blockchain‐based circular supply chain

Abstract: The growing importance of the circular economy has emphasised optimal utilisation of resources within the constraints of economic development and protection of the environment. Digital technologies associated with Industry 4.0, such as blockchain, facilitate the implementation of circular economy principles throughout the supply chain. However, because blockchain implementation in the supply chain is still in the early stages, real‐world examples of the blockchain‐based circular supply chains (CSCs) are limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 103 publications
(186 reference statements)
2
61
0
Order By: Relevance
“…to be the factors that favour pilot development projects in case of BT implementation in SC. Kayikci et al (2022aKayikci et al ( , 2022b in their review paper reported that under the umbrella of PPT (people, process, and technology), there were clear opportunities and impediments in case of people and technology. Massive benefits that arose out of implementing BT in SC especially in Food SC outweighed the risks.…”
Section: Bt Features Citationsmentioning
confidence: 99%
“…to be the factors that favour pilot development projects in case of BT implementation in SC. Kayikci et al (2022aKayikci et al ( , 2022b in their review paper reported that under the umbrella of PPT (people, process, and technology), there were clear opportunities and impediments in case of people and technology. Massive benefits that arose out of implementing BT in SC especially in Food SC outweighed the risks.…”
Section: Bt Features Citationsmentioning
confidence: 99%
“…Furthermore, Yadav and Singh proposed an incorporated principal component analysis and Fuzzy-DEMATEL to study the use of blockchain technology in sustainable supply-chain management [19]. In addition, Kayikci et al examined CSFs for blockchain-based circular supply chains (CSCs) through a short systematic literature review and using the integrated fuzzy cognitive mapping and fuzzy best-worst method (FCM-FBWM) [20]. Finally, Elhidaoui et al proposed a conceptual framework of a green supply-chain management (GSCM) model to investigate the critical success factors (CSFs) of blockchain-technology (BCT) adoption in green supply-chain management [21].…”
Section: Related Workmentioning
confidence: 99%
“…Among the leading studies looking at the impact of implementing the BCT factors is the publication of Kayikci et al (2022), oriented in the circular economy, presenting a model for identifying critical success factors. The authors also emphasise the need for cooperation and the strengthening of supply chains.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%